1997
DOI: 10.1128/jvi.71.11.8124-8132.1997
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in integrase can compensate for mutations in the simian immunodeficiency virus att site

Abstract: Sequences at the left terminus of U3 in the left long terminal repeat (LTR) and at the right terminus of U5 in the right LTR are important for integration of retroviral DNA. In the infectious pathogenic molecular clone of simian immunodeficiency virus strain mac239 (SIVmac239), 10 of the 12 terminal base pairs form an imperfect inverted repeat structure (5 TGGAAGGGATTT 3 [nucleotides 1 to 12] and 3 ACGATCCCTAAA 5 [nucleotides 10279 to 10268]). Nineteen different mutant forms of SIVmac239 proviral DNA with chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…For example, there is biochemical evidence that Lys-136 and Lys-159 can interact with viral DNA (27,51). Moreover, recent genetic studies showed that a mutation in simian immunodeficiency virus IN at the position analogous to Lys-136 in HIV-1 IN can compensate for mutations near the viral DNA termini (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is biochemical evidence that Lys-136 and Lys-159 can interact with viral DNA (27,51). Moreover, recent genetic studies showed that a mutation in simian immunodeficiency virus IN at the position analogous to Lys-136 in HIV-1 IN can compensate for mutations near the viral DNA termini (14).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with these in vitro studies, further experiments using the in vivo system are necessary for new insight into retroviral integration. Interestingly, the recent studies of Du et al (14) showed that a mutation in IN can compensate for mutations in simian immunodeficiency virus att.…”
Section: Figmentioning
confidence: 99%
“…These in vitro studies have greatly increased our understanding of the molecular mechanism of retroviral integration. However, recent studies (14,19,34,38,45) have indicated some differences or discrepancies between results of in vitro and in vivo assays. These discrepancies may reflect differences due to experimental conditions between in vitro and in vivo conditions.…”
mentioning
confidence: 99%
“…2). Mutants 1A2, 1B1, and 1B2 contained the same base changes as those previously studied in SIV (9). Whereas compensatory changes were incorporated into mutant 1B1 at U5 positions 43 to 45, these upstream bases were left unchanged in mutant 1B2.…”
Section: Hiv-1 Intasome Sequences Preferentially Cleaved During Mm-pcmentioning
confidence: 91%
“…Positions 5 to 7 from each terminus have been shown to be important for simian immunodeficiency virus (SIV) integration in infected cells (9). Mutants 1A1, 1A2, 1B1, and 1B2 targeted these sequences in HIV-1 (Fig.…”
Section: Hiv-1 Intasome Sequences Preferentially Cleaved During Mm-pcmentioning
confidence: 99%